Fast fashion, fashion brands & sustainable consumption - Abreu, Maria José (2019)
The phenomenon of fast fashion chains is due to the way this business model manages its production chain and supplies. Combining the quick response to the agile, lean retailing and leagile processes, it is possible to deliver products to retail outlets in a few weeks, in response to growing consumer demand for new goods. The excessive consumption of fast fashion is also due to social media involves issues such as sustainability in fashion consumption and work practices within companies and their suppliers. On the other hand, the awareness of the concern with the consequences of this consumption gives rise to new ways of consuming and producing fashion causing less impact both environmental and social.